First domino tile in the social innovation process: Idea creation of university students - Yıldırım, Nihan; Ansal, Hacer (2016 Portland International Conference on Management of Engineering and Technology (PICMET), 2016)
Interrelations between creativity, innovativeness and entrepreneurial skills of individuals have long been discussed in the literature. Due to the challenges regarding their measurement, most studies focused on the intentions rather than the outcomes. The idea generation that requires creativity is the first stage of social innovation. The young population's creative potentials in participating social innovation practices deserve a special attention as they play a critical role in the innovativeness and entrepreneurship of societies. This study aims to explore the factors that determine the creative intentions of university students that are important in generating social innovation projects. A structured survey based on the literature was conducted among 600 management and engineering students from 3 universities from the different percentiles of the Entrepreneurial and Innovative University Index for 2012 of the Turkish Ministry of Science, Industry and Technology. The survey included questions on the demographic characteristics, environmental factors, motivators, university/institutional context, perceptions and creative thinking attitudes. By conducting reliability and factor analysis, accuracy and validity of data is tested and the impact factors were identified. Findings reveal that visionary attitude, curiosity, exploration and learning, attitude for own creativity, self-esteem, perception about the learnability of creativity, university and social environment are components of creative thinking intentions of students and some of these factors vary by year of study and university.
Keywords: Entrepreneuriat; Europe; Innovation sociale; Réservé UdeM; Rôle des universités; Université

First domino tile in the social innovation process: Idea creation of university students - Yıldırım, Nihan; Ansal, Hacer (2016 Portland International Conference on Management of Engineering and Technology (PICMET), 2016)
Interrelations between creativity, innovativeness and entrepreneurial skills of individuals have long been discussed in the literature. Due to the challenges regarding their measurement, most studies focused on the intentions rather than the outcomes. The idea generation that requires creativity is the first stage of social innovation. The young population's creative potentials in participating social innovation practices deserve a special attention as they play a critical role in the innovativeness and entrepreneurship of societies. This study aims to explore the factors that determine the creative intentions of university students that are important in generating social innovation projects. A structured survey based on the literature was conducted among 600 management and engineering students from 3 universities from the different percentiles of the Entrepreneurial and Innovative University Index for 2012 of the Turkish Ministry of Science, Industry and Technology. The survey included questions on the demographic characteristics, environmental factors, motivators, university/institutional context, perceptions and creative thinking attitudes. By conducting reliability and factor analysis, accuracy and validity of data is tested and the impact factors were identified. Findings reveal that visionary attitude, curiosity, exploration and learning, attitude for own creativity, self-esteem, perception about the learnability of creativity, university and social environment are components of creative thinking intentions of students and some of these factors vary by year of study and university.
Keywords: Entrepreneuriat; Europe; Innovation sociale; Réservé UdeM; Rôle des universités; Université